SISTEM KELISTRIKAN BERBASIS SOLAR PANEL UNTUK RUMAH NELAYAN TRADISIONAL - Muqimuddin Muqimuddin; Hery Sunarsono; Assaidatul Husna (Universitas Muhammadiyah Tapanuli Selatan, 2022)
Limitations and the absence of electricity will disrupt the continuity of people activities. This is because electricity is one of the needs of the people and is felt to be very important. The availability of electricity, which is supported by power plants sourced from fossil fuels, certainly burdens the lower middle class community, including the fishing community. The solution that can be implemented to reduce the burden and dependence of the community on fossil fuels as a source of electrical energy is the use of solar energy. Indonesia has good potential when using solar energy as an alternative energy for power generation. This is because Indonesia is a tropical country that has abundant solar energy potential. Thus, this abundant solar resource is expected to meet household-scale electricity needs in remote areas that have not been reached by the State Electricity Company (PLN). PLTS in this service is carried out to meet electricity needs independently in residential homes that will be used day and night. The type of residential house used is a simple house type, with a total daily electrical power requirement of 1.314Wh and added 20% so that the total need is 1,576.8 Wh.